Answer:
y=2x+6 ; x+y=51
Step-by-step explanation:
assuming x is one number and y is the other -
one number (y) is 6 more (+6) than twice another (2x) -
using that knowledge we form an equation -
y=2x+6
the sum (x+y) is 51
using this knowledge we can make the equation -
x+y=51
now you have -
y=2x+6 or 2x-y=-6
x+y=51
using system of equations -
you add the equations -
3x=45
x=15
y=51-x => y=36
hope this helps!!
I = p * r * t
264 = p * .06 * 2
264 = .12p
Divide both sides by .12
p = $2200
Answer
(x+3) -5
Step-by-step explanation:
plug the values into the parent transformation equation to its rightful places